Adverse Effect of Periodontal Disease on Quality of Life - Sashikant Sethy1 , Sourav Chandra Bidyasagar Bal2 , Radhaprasanna Dalei2 , Gunjan Srivastav3 , Asima (Institute of Medico-legal Publications Pvt Ltd, 2020)
Periodontal disease represents various chronic inflammatory state of marginal, attach and free gingivaaround the tooth, alveolar bone, various types of periodontal ligaments which attach the tooth to the boneor anchorage system of tooth, all are tooth-supporting system. The disease of supporting the structure of thetooth starts from a mild form of gingival inflammation. The use of smoke tobacco is a topmost modifiablerisk factor for severe periodontal disease. The use of smoke tobacco has various links with periodontaldisease severity. From the various survey it is found that periodontal condition is worst among Smokedtobacco users than non-users. Giving proper treatment to various periodontal diseases is a great challenge,because at the early stage same patients are not aware of these things. To date there is not some bleeding fromgum, mild pain maximum patient doesn’t aware of these things. When bleeding from gum during hard foodchewing, hard or normal brushing patients reports complain. Gingivitis periodontitis like disease are nonviolent, some time asymptomatic but they have a negative impact on mastication, esthetic of individuals.Sometimes it has effects the speech of people. Disruptions in the function of neutrophils can lead to developgingivitis periodontitis. Down syndrome, neutropenia can lead to periodontal disease. Developing age canleads to periodontitis.